Praise and blame : moral realism and its applications - Robinson, Daniel N., 1937- (New forum books., 2002)
How should a prize be awarded after a horse race? Should it go to the best rider, the best person, or the one who finishes first? To what extent are bystanders blameworthy when they do nothing to prevent harm? Are there any objective standards of moral responsibility with which to address such perennial questions? In this fluidly written and lively book, Daniel Robinson takes on the prodigious task of setting forth the contours of praise and blame. He does so by mounting an important and provocative new defense of a radical theory of moral realism and offering a critical appraisal of prevailing alternatives such as determinism and behaviorism and of their conceptual shortcomings. The version of moral realism that arises from Robinson's penetrating inquiry--an inquiry steeped in Aristotelian ethics but deeply informed by modern scientific knowledge of human cognition--is independent of cognition and emotion. At the same time, Robinson carefully explores how such human attributes succeed or fail in comprehending real moral properties. Through brilliant analyses of constitutional and moral luck, of biosocial and genetic versions of psychological determinism, and of relativistic-anthropological accounts of variations in moral precepts, he concludes that none of these conceptions accounts either for the nature of moral properties or the basis upon which they could be known. Ultimately, the theory that Robinson develops preserves moral properties even while acknowledging the conditions that undermine the powers of human will.